Global Governance: CSR and the Role of the UN Global Compact - Voegtlin, Christian (Journal of business ethics, 2014)
The article discusses the role of the UN Global Compact (UNGC) in the emerging global corporate social responsibility infrastructure. It evaluates the debate around the effectiveness and legitimacy of the UNGC alongside the arguments of its supporters and critics and thereby introduces the Thematic Symposium contributions. The article further identifies three theoretical perspectives that are used by scholars to discuss the performance of the UNGC: economic, socio-historical, and normative. It proposes that these perspectives can serve as generic distinctions with direct relevance for the evaluation of the UNGC. Once the perspective is chosen, it drives towards a certain purpose which implies assumptions and design features with regard to the UNGC. Finally, the article offers a future research agenda, emphasising the research needed on the UNGC in four areas: the identification of processes and influence mechanisms; legitimacy and effectiveness; local networks and regional development; and the interface of the UNGC and responsible leadership.